Rythm in Bronze, New Music for the Malaysian Gamelan - Patricia Matusky (Wacana Seni Journal of Arts Discourse, 2002)
A concert entitled "Rhythm in Bronze" took place in the mid-1990s in Kuala Lumpur and featured pieces for the Malay gamelan by various artists, principally Sunetra Fernando "who trained the gamelan and prepared several pieces for that performance. I had the pleasure of writing about the gamelan in the program booklet for that first "Rhythm in Bronze," produced by the Five Arts Centre.